Jogos teatrais, pensamento simbólico e conhecimento intuitivo: diálogos entre Viola Spolin e Jean Piaget - Tancrede, Onira de Avila Pinheiro (2017)
The aim of this study is to relate the methodological aspects of theater games, such as developed by Viola Spolin (1906-1994), and symbolic play (jeu symbolique) as presented by Jean Piaget (1896-1980). This research analyzes the symbolic function and the symbolic games ([1945]) at the thought of Piaget and the improvisational games of Viola Spolin ([1963]). From this perspective, establish dialogues in their entertainment and educational way and shows how the knowledge of these symbolic characteristics and the intuitive knowledge can influence the driving proposals for theater education in public schools with children. This dissertation departs from the meaning established by the relationship between meaning/significant with the intuitive intelligence, which are elements presents in the theatrical play.